TEORI THE SPREAD OF ISNAD (Telaah Atas Pemikiran Michael Allan Cook) - Ramdhani, Imam Sahal (Jurnal Studi Ilmu-ilmu Al-Qur'an dan Hadis, 2015)
erchange-newline"> It is closely related to “Common Link” phenomenon whom plenty of West Scholar on Hadith dealing their researches on it. By looking at thisphenomenon, this paper is trying to review Cook’s idea about common linkand the process of theory the spread of isna>d ‘s aplication in conceivingthe common link phenomenon. Based on this research, we understand thatCook brought a different point of view to the Common Link phenomenonwhich is poured forth on his critics to the Schachtian’s theory. For Cook,there are two essential points related to Common Link. First, Common Linkcan’t be justifid as a hadith counterfeiter. It is because Common Link tosome exctent is an engineering-work from the other narrator (periwayat).Second, Common Link can’t be a basic of hadith’s dating. Then, Cook’spoint of view pulled down Commen Link theory.